A case of an asymptomatic Plasmodium falciparum infection followed by a symptomatic Plasmodium ovale infection in a soldier deployed to South Sudan - Choon Mee Kim; Jun-Won Seo; Da Young Kim; Na Ra Yun; Beomgi Lee; You Mi Lee; Munawir Muhammad; Dong-Min Kim (Malaria Journal)
Abstract Background Asymptomatic malaria poses a significant challenge to malaria eradication efforts and delays global elimination strategies. Mixed infections are also a major concern, as they frequently relapse, increase the risk of severe malaria, require more accurate diagnosis for appropriate treatment, and contribute to the development of drug resistance. Case presentation A 25-year-old soldier was diagnosed with malaria following deployment in South Sudan. A comprehensive survey identified an asymptomatic Plasmodium falciparum infection, confirmed by peripheral blood smear and polymerase chain reaction (PCR). Despite being discharged after treatment, the patient developed fever and other symptoms one month later. Subsequent laboratory tests confirmed Plasmodium ovale infection based on peripheral blood smears and PCR. Conclusion This case underscores the importance of molecular detection for surveillance and vigilant follow-up in malaria management, particularly among patients with a history of deployment in endemic regions. The detection of P. ovale after treatment for P. falciparum highlights the need for increased awareness and testing for mixed infections to ensure effective malaria control strategies.